COMMUNICATIVE COMPETENCE AS A PEDAGOGICAL CATEGORY - Крилова, К. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article deals with the concept of «communicative competence», which is mentioned in various scientific sources, and various authors look at this. Pedagogical category as one of the most important characteristics of professionally significant future specialist. Also, given the author’s definition of communicative competence